Description of four new species related to Fissocantharis novemexcavatus (Wittmer, 1951) (Coleoptera, Cantharidae) from China - Yang, Yuxia; Li, Limei; Yang, Xingke (Zootaxa, 2015)
Four new species related to Fissocantharis novemexcavatus (Wittmer, 1951) are described, F. safranekimima sp. nov. (CHINA: Shaanxi), F. septangula sp. nov. (CHINA: Shaanxi), F. guizhouensis sp. nov. (CHINA: Guizhou) and F. novemoblonga sp. nov. (CHINA: Zhejiang, Anhui), which are illustrated with habitus and antennae of males, abdominal sternites VIII of females and genitalia of both sexes. A key for identification of the species of F. novemexcavatus species complex is presented.